(untitled) (Bangladesh Journal of Medical Science, 2015)
Lipoma is the benign tumor occurring at any anatomical site where fat is present. It may be evident for 1 to 5 percent of the entire benign tumor of the oral cavity. Lipoma of the tongue is extremely rare because tongue is totally devoid of fat cell. In this case study we report a case of lipoma of tongue. A 45 years old Bangladeshi female patient presented with this benign tumor at the left lateral border with dorsal and ventral surface of the tongue for which complete tumor excision was done. Bangladesh Journal of Medical Science Vol.14(3) 2015 p.302-304